PENGARUH PENCAMPURAN MINYAK TANAH DENGAN BAHAN BAKAR MINYAK DIESEL, BIODIESEL DAN LAINNYA - REVIEW - Annisa Bhikuning; Muhammad Hafnan; Jefa Danar Indra Wijaya (Jurnal Rekayasa Mesin, 2022)
The use of diesel oil has been proven to increase exhaust emissions which will have an impact on the environment. Mixing diesel oil with other fuels can reduce exhaust emissions and increase combustion efficiency. This article discusses the review of mixing kerosene with diesel oil and biodiesel. The method was the fuel are running in the diesel engine and calculated the performance and emissions in the engine. The fuel properties of mixing kerosene with diesel oil and biodiesel can reduce the level of viscosity and specific gravity of the fuel and increase the calorific value which will have an impact on improving the atomization in combustion. In addition, mixing diesel oil and kerosene can reduce emissions such as CO2, CO, HC, particulate, and opacity. However, mixing kerosene with biodiesel can increase NOx emissions. In addition, the addition of kerosene in diesel oil can lead to low fuel consumption in diesel oil. The addition of kerosene with biodiesel will increase thermal efficiency. Therefore, it can be concluded that the addition of kerosene into diesel oil and biodiesel can improve engine performance in the engine and reduce some exhaust emissions.